2013
DOI: 10.7314/apjcp.2013.14.7.4235
|View full text |Cite
|
Sign up to set email alerts
|

Sulforaphane is Superior to Glucoraphanin in Modulating Carcinogen-Metabolising Enzymes in Hep G2 Cells

Abstract: Glucoraphanin is the main glucosinolate found in broccoli and other cruciferous vegetables (Brassicaceae). The objective of the study was to evaluate whether glucoraphanin and its breakdown product sulforaphane, are potent modulators of various phase I and phase II enzymes involved in carcinogen-metabolising enzyme systems in vitro. The glucosinolate glucoraphanin was isolated from cruciferous vegetables and exposed to human hepatoma cell line HepG2 at various concentrations (0-25 µM) for 24 hours. Glucoraphan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 25 publications
1
11
0
Order By: Relevance
“…Sulforaphane [1-isothiocyanato-(4R)-(methylsulfinyl) butane: CH 3 S(O)(CH 2 ) 4 -N=C=S] is a small (MW = 177.29) aliphatic lipophilic organosulfur molecule which is not present in cruciferous or other plants (Supplementary Data, Figure 1, in Supplementary Material available online at http://dx.doi.org/10.1155/2016/7857186 ). Instead, plants of Brassica genus contain a biologically inactive precursor compound, glucoraphanin (GRN), which is contained within a plant cell vacuole together with an enzyme, myrosinase (MYR), which is separately compartmentalized [ 39 ]. It is when the plant cell ruptures and the GRN and MYR come into contact that sulforaphane is enzymatically produced [ 40 ] (Supplementary Data, Figure 2).…”
Section: Influencing Signaling Pathwaysmentioning
confidence: 99%
“…Sulforaphane [1-isothiocyanato-(4R)-(methylsulfinyl) butane: CH 3 S(O)(CH 2 ) 4 -N=C=S] is a small (MW = 177.29) aliphatic lipophilic organosulfur molecule which is not present in cruciferous or other plants (Supplementary Data, Figure 1, in Supplementary Material available online at http://dx.doi.org/10.1155/2016/7857186 ). Instead, plants of Brassica genus contain a biologically inactive precursor compound, glucoraphanin (GRN), which is contained within a plant cell vacuole together with an enzyme, myrosinase (MYR), which is separately compartmentalized [ 39 ]. It is when the plant cell ruptures and the GRN and MYR come into contact that sulforaphane is enzymatically produced [ 40 ] (Supplementary Data, Figure 2).…”
Section: Influencing Signaling Pathwaysmentioning
confidence: 99%
“…A number of phytochemicals have been considered as potential cancer chemopreventive agents, e.g., glucosinolates (GLs) ( Figure 1 ), major components found in cruciferous vegetables which over the years have been identified as potential anti-carcinogens against many common cancers [ 4 , 5 , 6 , 7 , 8 ]. GLs are readily hydrolysed upon tissue damage by the myrosinase enzyme into several active compounds, including isothiocyanates that are believed to be responsible for the chemopreventive activity reported in many studies [ 9 , 10 , 11 , 12 , 13 ]. These compounds bring about beneficial changes in cancerous cells providing convincing evidence that isothiocyanates can be potentially developed into anticancer agents of therapeutic benefit to humans.…”
Section: Introductionmentioning
confidence: 99%
“…gemmifera Zenker ) and cabbage ( Brassica oleracea L. var. capitata L), and has an indirect antioxidant activity . A line of evidence has dissected that the antioxidant and antitoxic characteristics of SFN are most easily to involve in the activation of the Nrf2 gene in experimental models .…”
Section: Introductionmentioning
confidence: 99%
“…capitata L), and has an indirect antioxidant activity. [17,18] A line of evidence has dissected that the antioxidant and antitoxic characteristics of SFN are most easily to involve in the activation of the Nrf2 gene in experimental models. [19] Moreover, it has been reported that SFN has chemotherapeutic properties including antiproliferative properties, the blockade of angiogenesis and induction of tumour cell apoptosis.…”
Section: Introductionmentioning
confidence: 99%